2020
DOI: 10.3389/fpsyt.2020.581149
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Implementation, and Acceptability of a Telehealth Comprehensive Recovery Service for People With Complex Psychosis Living in NYC During the COVID-19 Crisis

Abstract: Introduction The COVID-19 crisis and subsequent stay-at-home orders have produced unprecedented challenges to the dissemination of recovery oriented behavioral health services (RS) that support the treatment of those with complex psychosis (CP).This population has typically been managed with in-person pharmacotherapy and/or RS, with the goals of relieving symptoms, improving life satisfaction and increasing community engagement. COVID-19 related social distancing measures have required rapid shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Several studies e.g. (87, 99), mention the need for an agreed ‘Zoom etiquette’ for service users, including attire, audio/visual set-up and background distractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies e.g. (87, 99), mention the need for an agreed ‘Zoom etiquette’ for service users, including attire, audio/visual set-up and background distractions.…”
Section: Resultsmentioning
confidence: 99%
“…(117). Most studies which examined impact on attendance reported no adverse effects on attendance rates after introducing telemental health: there was either no difference in missed appointments when comparing remote to face-to-face care (46, 87), or non-attendance after adoption of telemental health decreased (80, 92, 104). Further details about adoption of telemental health across studies can be found in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…This may be particularly true of psychotic disorders, which are generally considered the most serious form of mental illness and associated with high disability weights [9]. Clinical case reports and commentaries have posited that the COVID-19 pandemic will lead to widespread reductions in service utilization and subsequent increases in acute symptom exacerbations in those who had already been diagnosed with a psychotic disorder prior to the pandemic [35,40,44]. There is also fear that reduced access to healthcare, social isolation, and reduced physical activity may lead those at clinical high risk (CHR) for developing psychosis to transition to illness onset [6,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…O app em avaliação na Espanha, também com base na TCC -PsyCovidApp, uma intervenção para profissionais de saúde a partir de habilidades emocionais, estilo de vida, estresse no trabalho, suporte social e ferramentas práticas, demonstrou ser muito positivo 1 . Contudo, dificuldades relacionadas à falta de conectividade e acesso em áreas rurais devem ser consideradas 35. Relacionado com as intervenções em saúde mental e os respectivos aplicativos virtuais disponíveis, o programa de cuidado iCAN-DO indicou benefícios aos usuários com câncer e com sintomas como ansiedade e depressão 37 , assim como outros tipos de intervenção como Step-by-Step e MOOD, que também indicaram a melhora nos sintomas de depressão, trazendo bem-estar aos participantes 36,48 , o que corrobora com outros estudos com aplicativos que revelaram que indivíduos com sintomas psicológicos graves como psicose, podem beneficiar-se 19,21,49 . Entretanto, também podem apresentar dificuldades no uso da internet, não envolvendo-se de forma contínua 49,50 .…”
Section: Discussionunclassified
“…As intervenções envolveram atendimentos para redução de ansiedade e sintomas depressivos, transtorno alimentar e TDAH, com usuários do sistema de saúde e de clínicas de tratamento, por meio de ligações telefônicas e videoconferências. O potencial do uso da linha telefônica mostrou impacto para além da redução de problemas psicológicos, como ansiedade, depressão e transtorno de pânico [13][14][15][16][17] , e no tratamento de pacientes com psicoses 18,19 , tendo em vista o medo de contágio com o vírus. O uso da telessaúde [20][21][22][23][24][25][26] e da psicoterapia on-line ou por telefone 14 para os profissionais de saúde no enfrentamento da pandemia foi positivo, e com menor número de desistência quando comparada ao atendimento presencial 27,28 .…”
Section: Fonte: Secchi Et Al (2021)unclassified